Detection of erythropoiesis stimulating agent Luspatercept after administration to healthy volunteers for antidoping purposes. Issue 11 (7th July 2022) - Marchand, Alexandre; Miller, Geoff; Martin, Laurent; Gobbo, Coralie; Crouch, Andre K.; Eichner, Daniel; Ericsson, Magnus
Abstract: Luspatercept (Reblozyl®) is a newly approved anti‐anemic drug prohibited by the World Anti‐Doping Agency. It promotes erythropoiesis by limiting apoptosis of immature erythroblasts and the risk of misuse by athletes for doping is high. Proposed detection methods have been published recently but only evaluated in vitro. The objective of this study was to perform the first administration of luspatercept in healthy volunteers for antidoping purpose and to evaluate the detectability in serum, dried capillary blood spots (DBS, collected using TASSO M20 device), and urine. Indirect detection was also evaluated by analyzing hematological parameters for the Athlete Biological Passport. Four volunteers (two males, two females) received one subtherapeutic dose of luspatercept (0.25 mg/kg) followed 3 weeks after by a second dose. Samples were collected from before administration until 7 weeks after the second dose. After immunopurification, electrophoretic separation SDS‐/SAR‐/IEF‐ polyacrylamide gel electrophoresis (PAGE), and immunodetection, luspatercept was detected at high levels in serum until the end of the collection, sign of a very slow elimination and similarly detected unchanged at lower levels in urine from 2 days after the first administration until 7 weeks postadministration. DBS showed also the same long window of detection. Luspatercept effects were however of limited amplitude on hematological markers, and only two subjects presented atypical points outside the physiological limits during the study. The direct detection method was very efficient, and change of electrophoretic method and detection antibody can be used for confirmation of suspicious samples. Abstract : This study was to perform the first administration of drug Reblozyl (Luspatercept) for testing doping detection. Detection was possible with serum, urine, and DBS for over 70 days. SDS‐PAGE, SAR‐PAGE or IEF‐PAGE method can be used for confirmation. Indirect detection by looking at hematological parameters variation was less efficient.